Unraveling the Mediating Role of Buoyancy in the Relationship Between Anxiety and EFL Students’ Learning Engagement - Liu, Honggang; Zhu, Zhengfeng; Chen, Bin (Perceptual and motor skills, 2025)
Recent investigators have illuminated the crucial role of positive psychology in learning English as a Foreign Language (EFL). However, little is known about academic buoyancy as a potential mediator in the relationship between foreign language anxiety and learners’ academic engagement in English learning. To address this gap, we adopted a quantitative approach to explore these links. We surveyed 970 Chinese high school EFL students to measure their English learning anxiety, academic buoyancy, and learning engagement. Of the four dimensions of engagement – behavioral, emotional, cognitive, and agentic engagement – we discarded the emotional and cognitive dimensions of academic engagement in factor analyses. Structural equation modelling indicated that English learning anxiety directly predicted behavioral but not agentic engagement, and academic buoyancy partially mediated between English learning anxiety and behavioral engagement and completely mediated between English learning anxiety and agentic engagement. These results provide insights for EFL teachers seeking to enhance students’ language learning experiences.